Digitalisasi Infrastruktur Pertanian untuk Mendukung Ketersediaan Pangan Nasional - Ardiana, Wiwik; Purnomo, Didit (Jurnal Sosial Ekonomi Pertanian, 2025)
Digital infrastructure factors such as Base Transceiver Station (BTS) and internet-using households play a crucial role in driving agricultural transformation in Indonesia, although their distribution remains uneven. Data BPS for the period 2019–2021 indicate an increase in the number of BTS across provinces, yet the level of internet penetration in agricultural households is still constrained by digital literacy and network quality. This condition raises the question of how far digitalization can enhance corn productivity as one of the nation’s strategic commodities. This study aims to analyze the influence of harvested area, informal labor in the agricultural sector, BTS, and internet-using households on corn production in Indonesia. The method employed is panel data regression with a Fixed Effect Model (FEM), using secondary data from 34 provinces during the 2019–2021 period. The results show that harvested area and BTS have a significant positive effect on corn production, while informal labor in the agricultural sector has no significant effect. In contrast, internet-using households have a significant negative effect, suggesting that internet access without agricultural digital literacy has not been utilized optimally. The main contribution of this study lies in integrating traditional factors (harvested area, informal labor in the agricultural sector) and digital factors (BTS, internet-using households) into a single national model. This research emphasizes that agricultural digitalization requires equitable infrastructure development and stronger digital literacy to enhance productivity and strengthen food security. These findings can provide important input for the government in shaping the direction of agricultural digitalization policies that are more inclusive and sustainable. Keywords:  Corn production; agricultural digitalization; digital literacy; food security.